ENVIRONMENTAL MANAGEMENT CONTRIBUTED TO LEARNING FOR STUDENTS AT RAJAVINITBANGKHEN SCHOOL UNDER THE JURISDICTION OF BANGKOK SECONDARY EDUCATIONAL SERVICE AREA OFFICE 2 - Kettanom, Thasporn; Ratanapitakdhada, Chookwan (Journal of MCU Nakhondhat, 2024)
The objectives of this research are 1) To study the level of providing an environment that is conducive to student learning 2) To study guidelines for developing an environment that is conducive to student learning. Description The sample groups used in the research are: There were 313 students at Ratchawinit Bangkhen School by comparing the sample size proportions from Krejci and Morgan's tables. Then stratified random sampling was used. using simple classes and randomization By drawing lots The tool used is a questionnaire. It is characterized by a 5-level evaluation scale and a structured interview. It has a consistency index ranging from 0.67-1.00 with a confidence value of 0.97. Statistics used in data analysis include percentages, means, standard deviations and content analysis. The research results found that Creating an environment conducive to learning for students at Rachawinit Bangkhen School Overall it is at a high level. When considering each aspect, it was found that it was at a high level in every aspect. They are sorted by average from highest to lowest as follows: Learning management Group of friends Administration and buildings as for guidelines for developing an environment that is conducive to learning for students at Rachawinit Bangkhen School There are guidelines for development as follows: 1) Learning management Learning should be organized by using local wisdom. Technology and media that are consistent with the community context to create a teaching atmosphere for students to gain knowledge and be able to put it into practice. 2) Peer group aspect Teachers cooperate in maintaining the school's reputation and image. There are activities both inside and outside the classroom that encourage students to learn and develop themselves in every aspect. 3) Administrative aspect There should be an opportunity for students to express their opinions with the school administration. 4) Buildings and facilities There should be a place for learning resources, a library, a science park. Agricultural garden inside the school